Effects of betalains on atherogenic risk factors in patients with atherosclerotic cardiovascular disease. Issue 12 (14th November 2019) - Rahimi, Parisa; Mesbah-Namin, Seyed Alireza; Ostadrahimi, Alireza; Abedimanesh, Saeed; Separham, Ahmad; Asghary Jafarabadi, Mohammad
Abstract : After consumption of betalain-rich supplements of red beetroot and betacyanins-rich supplements of Opuntia stricta, the betanin appears in urine and plasma to improve the lipid profile, blood pressure, homocysteine and glucose levels of the patients. Abstract : This study evaluated the potential impacts of supplementation with betalain-rich extracts of foods on some atherosclerotic risk factors in coronary artery disease patients. During an acute phase, 48 male patients received about 50 mg betalain/betacyanin, and their blood and urine samples were collected at 3, 8, and 24 hours after supplementations. Also, in a pilot randomized crossover trial, these participants were allocated to two-week interventions (a betacyanin-rich supplement of Opuntia stricta, a betalain-rich supplement of red beetroot and a placebo) with two-week washout periods. Then, their plasma samples were collected at the baseline after a two-week period. The concentrations of betanin in plasma and urine samples were determined using HPLC. Also, homocysteine and glucose levels, lipid profile, and blood pressure were analyzed. Additionally, quality of life and dietary intake were assessed. After these interventions, minimal amounts of betanin were found in plasma and about 0.13–0.93% in urine. Also, both supplements significantly decreased the concentration of homocysteine, glucose, total cholesterol, triglyceride, and LDL. Also, betalain-rich supplements lowered both systolic and diastolic blood pressures. Nevertheless, the clinically meaningful changes were only found in the case of Hcy, LDL, and non-HDL-c concentrations. It seems that food sources of betalains can be considered as functional foods because they improve the lipid profile and levels of homocysteine, glucose, blood pressure, and quality of life to some extent.